Efficacy of intense pulsed light therapy in the treatment of idiopathic hirsutism - Mehmood, Bushra Tahir; Qayum Khan, Abdul Qayum; Rashid, Tariq; Ashraf, Sumeet (Journal of Fatima Jinnah Medical University, 2019)
Background: Hirsutism is a male pattern of terminal, coarse and medullated hair growth in females at androgen dependent sites. Idiopathic hirsutism is the second most important and frequent cause of hirsutism after polycystic ovarian syndrome. It has an adverse impact on psychosocial status of patients. Lasers- and light-based treatment modalities are now increasingly used and yield long lasting reduction of unwanted facial hair. Light-based modalities include intense pulsed light (IPL) and E-Light. This study aims to assess the efficacy of IPL in the treatment of idiopathic hirsutism. Subjects and methods: This prospective interventional study was carried out from 1st June 2015 to 29th Feb 2016, on female patients of age between 20-41 years, having idiopathic hirsutism with chin hair of Grade 4 Ferriman and Gallewey (F-G) score. The patients were not on any prior oral, topical or laser therapy for hirsutism during last 6 months and had no active infection or eczema at treatment site. Patients were treated with IPL having fixed parameters. Baseline hair count was noted before treatment and then hair count was done at 1 month after 6 complete sessions, each session being 1 month apart. Final hair count was done at 7th month from baseline and percentage hair reduction was calculated. Effectiveness was evaluated in terms of percentage of patients showing >50% hair reduction. Results: Eighty patients with mean age 28 years were assessed. Fifty-four patients (67.5%) showed >50% hair reduction while 26 patients (32.5%) showed <50% hair reduction at follow up of 1 month after 6 complete sessions. No significant side effects were observed except mild diffuse and/or perifollicular erythema and the treatment was tolerated well by the patients. Conclusion: Intense pulsed light (with fixed parameters) is an effective treatment modality for the treatment of idiopathic hirsutism.